Program Literasi Budaya Baca sebagai Upaya Peningkatan Mutu Siswa (Single Case Study di SDN Sumbersari 3) - Bilkis, Zenita; Imron, Ali; Zulkarnain, Wildan (Proceedings Series of Educational Studies, 2024)
Abstract : This study aims to describe and analyze the development of literacy culture at Sumbersari 3 Public Elementary School, Malang City. This research uses a descriptive qualitative research method using a case study approach. Data collection techniques were carried out by interviewing, observing, and documenting school coordinators, teachers, and students. According to what will happen in the research, it can be seen that 1) literacy activities play a role in increasing students' interest in reading, 2) obstacles to carrying out literacy activities in schools include that every teacher must be able to embrace every student, every teacher must be able to anticipate if there are students who has less fast catching power, 3) the rides and infrastructure are sufficient. The quality of education at Sumbersari 3 Public Elementary School is a priority for the school, due to the assessment of the surrounding community by looking at the quality of the results from the school.Abstrak : Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis pengembangan budaya literasi pada Sekolah Dasar Negeri Sumbersari 3 Kota Malang. Penelitian ini menggunakan metode penelitian kualitatif deskriptif menggunakan pendekatan studi perkara. Analisi data menggunakan model interaktif. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi terhadap koordinator sekolah, pengajar, serta peserta didik. sesuai yg akan terjadi penelitian bisa dipandang bahwa 1) kegiatan literasi berperan pada menaikkan minat membaca peserta didik, 2) kendala pada melaksanakan aktivitas literasi pada sekolah antara lain ialah setiap guru wajib bisa merangkul setiap siswa, setiap guru wajib bisa mengantisipasi apabila ada peserta didik yang memiliki daya tangkap yg kurang cepat, 3) wahana serta prasarana telah cukup memadai. Kualitas mutu pendidikan pada Sekolah Dasar Negeri Sumbersari 3 sebagai prioritas bagi sekolah, sebab penilaian masyarakat sekitar dengan melihat kualitas hasil asal sekolah tersebut.